Preliminary Study: IQF Curriculum Evaluation Towards MBKM in Terms of Conceptual Model and Experts Judgments - Muhammad Jhoni; Fakhruddin Fakhruddin; Masrukhi Masrukhi; Sri Ratna Rahayu (Universitas Negeri Semarang, 2022)
The three profiles of the graduates of the Physics Education Study Program at UIN Raden Fatah Palembang are expected to be Physics Educators for Secondary Education, Physics Researchers, and Entrepreneurs. However, the facts on the ground are not so, so it is necessary to evaluate the curriculum. The purpose of this study is as an initial research for curriculum evaluation with a focus on the study of conceptual models and assessment of the implementation of the IQF curriculum. The approach used is Mix Methods with Qualitative and Quantitative design. The sample of this study was 100 alumni who graduated in 2018, 2019, 2020, 2021 and 2022. Data collection used a questionnaire via google forms for tracer studies, direct interviews with alumni and FGDs that presented expertudment to assess the weaknesses of the IQF curriculum. Data analysis used descriptive qualitative and quantitative. The results of the study resulted in several recommendations for Expert Judgment including; 1) The new curriculum is able to accommodate MBKM policies with various schemes offered, 2) Redesign the curriculum according to its content and the needs of the current world of work, 3) It is necessary to study several courses in order to follow the hierarchy and prerequisites of previous courses, 4) Review back The CPL of SKS courses that are too large such as Mechanics and Electricity and Magnetism, 5) Elective courses should be submitted to lecturers who support the profession/entrepreneur, 6) Adding courses that can introduce students to technology-based learning, 7) Adding an elective MK that provide special skills and in accordance with current developments, especially in the field of entrepreneurship